Keberdayaan KWT Madu Arum dalam Program Pekarangan Pangan Lestari Mendukung Ketahanan Pangan di Kecamatan Tasikmadu, Indonesia - Shabila Sekarwati; Suwarto Suwarto; Putri Permatasari (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Sustainable food yards are a garden-based crop cultivation program aimed at achieving family food security. Women's farmer groups are the main subjects implementing the sustainable food yards program in the Tasikmadu District. The implementation of the sustainable food yards program in Tasikmadu District continues to face challenges related to empowering KWT members. This study aims to examine the empowerment of KWT members, analyze the factors shaping their empowerment, and assess the influence of these factors on their empowerment in the sustainable food barn program. The population of this study was members of the Madu Arum KWT in Tasikmadu District, with a sample of 54 respondents. The data analysis method used multiple linear regression analysis. The results found that the empowerment of KWT members was influenced by age, non-formal education, family support, group role, extension worker role, and government support. This study is the first to identify variables that directly influence the empowerment of KWT members in Tasikmadu District, thereby providing a basis for policy interventions related to sustainable food yards. Strategic focus is essential to improve non-formal education, strengthen the role of groups, and optimize the important contribution of extension workers to achieve better empowerment and increase program effectiveness.